A hierarchical optimization model for energy data flow in smart grid power systems. (October 2015) - Jarrah, Moath; Jaradat, Manar; Jararweh, Yaser; Al-Ayyoub, Mahmoud; Bousselham, Abdelkader
Abstract: Environmental concerns and high prices of fossil fuels increase the feasibility of using renewable energy sources in smart grid. Smart grid technologies are currently being developed to provide efficient and clean power systems. Communication in smart grid allows different components to collaborate and exchange information. Traditionally, the utility company uses a central management unit to schedule energy generation, distribution, and consumption. Using centralized management in a very large scale smart grid forms a single point of failure and leads to serious scalability issues in terms of information delivery and processing. In this paper, a three-level hierarchical optimization approach is proposed to solve scalability, computational overhead, and minimize daily electricity cost through maximizing the used percentage of renewable energy. At level one, a single home or a group of homes are combined to form an optimized power entity (OPE) that satisfies its load demand from its own renewable energy sources (RESs). At level two, a group of OPEs satisfies energy requirements of all OPEs within the group. At level three, excess in renewable energy from different groups along with the energy from the grid is used to fulfill unsatisfied demands and the remaining energy are sent to storage devices. Abstract : Highlights: We examine the three scopes of smart grid systems. We write mathematical models to cover the different aspects in SG. We use linear optimization to solve the equations and yield optimal solutions. Hierarchical method achieves better distribution and cooperative scenario.